THE ANALYSIS OF ENERGY OPTIONS FOR CENTRAL KALIMANTAN PROVINCE - Debora debora; Vontas Alfenny Nahan (BALANGA: Jurnal Pendidikan Teknologi dan Kejuruan, 2013)
Kalimantan contributed 10.5% to the national GDP in 2008. Most of this contribution (7.5%) came from East Kalimantan, followed by West Kalimantan (1.2%), South Kalimantan (1.1%), and Central Kalimantan (0.8%). Even though Central Kalimantan’s contribution is still relatively small in terms of national GDP, in the coming years it become bigger and bigger as the energy resources in the neighboring provinces is decreasing. It is estimated that energy demand in Central Kalimantan will more than treble by 2025 - as compared with 2010 consumption level. Clearly, effective policy measures will be required to overcome current energy problems and to plan for the future and this is the main objective of the research. Two scenarios are developed in this research to better understand the wider consequences of strategies to meet rising demand not only in Central Kalimantan, but also in Kalimantan region. The first scenario is called (in this research) Business-As-Usual (BAU) which corresponds with the national energy blueprint for 2025. The other scenario is Renewable (REN) with 15% more of renewable energy in the primary energy mix. First recommendation offered here is to suggest that the rate of utilization of renewable energy should be increased. Other option is to develop energy infrastructure, pipelines for gas distribution or gas stations for gas-fueled vehicles. Other strategies include promoting the environmental conservation, public-private partnership for infrastructure development, promotion of research and development on energy issues, design of appropriate financial and legal frameworks and emphasis on capacity building and technology transfer.